Inguinal lymphadenopathy as a predicting factor for ipsilateral primary limb amputation after a successful endovascular treatment. Issue 130 (September 2020) - Raskin, Daniel; Khaitovich, Boris; Balan, Shmuel; Silverberg, Daniel; Rmeileh, Ahmad Abu; Halak, Moshe; Rimon, Uri
Highlights: Preprocedural CTA can be used to assess the presence of inguinal lymphadenopathy. Lymphadenopathy is associated with amputation after successful revascularization. Lymphadenopathy on CTA is linked to an overt infection associated with foot ulcer. Abstract: Purpose: To assess the correlation between inguinal lymph node characteristics and ipsilateral limb amputation rates in patients with ischemic foot ulcers after a successful endovascular treatment. Method: A retrospective review of patients who were endovascularly treated for ischemic foot ulcers between January 2015 and May 2017. Technical success was defined as arterial recanalization with stenosis less than 30 % and ankle brachial index improvement by > 0.2 after 24 h. Unilateral lymph node size, contrast enhancement, necrosis, and perinodular fat stranding were assessed on pre-procedural CTA. Primary endpoints were amputation and sepsis within 12 months following treatment. The relationship between lymph node characteristics and limb amputation and septic shock were examined. Results: Endovascular treatment of 202 limbs in 202 patients (135 males; median age 72.8 years [42.2–93.7]) was technically successful. Forty-two (20.8 %) patients underwent amputation, six (3 %) patients had septic shock. There was a significant difference in lymph node sizes between the amputated and the non-amputated limbs (P = 0.000). Lymph node characteristics (size, enhancement, necrosis, and perinodular fat stranding) were significantly related to amputation (P < 0.001). Patients with perinodular fat stranding or increased node size were 5.940 and 1.109 times more likely to undergo limb amputation, respectively. Lymph node characteristics were also significantly related to septic shock (P < 0.05). Conclusions: Certain lymph node characteristics are associated with amputation in patients with ischemic foot ulcers, after a technically successful endovascular treatment of the limb. Large lymph node size and perinodular fat stranding are predictive of limb amputation.